Chinese contributions to hospitality research: patterns of authorships and collaborations - Köseoglu, Mehmet Ali (2021)
The contributions by China-based authors to the burgeoning Chinese language tourism literature have been accompanied by the growing and well documented appearance in English-language journals by Chinese authors from both within and outside the country. However, there has been adequate quantification and evaluation of Chinese contributions to international hospitality research, including those leading to the formation of networks. The current study examines China-affiliated authorship networks and collaboration patterns in seven top-tier English-language hospitality journals. The authors deploy a bibliometric approach to analyze the evolution of such networks and patterns over three decades. Results of the study contribute to discussions on the progressive internationalization of hospitality research taking account of cultural backgrounds of its knowledge producers. Limitations and opportunities for future research are reflected.